Boys and girls as readers: what do the teachers think? - Mohd. Asraf, Ratnawati; Abdullah, Hazlina (American Scientific Publishers, 2017)
This paper discusses one part of the findings of a study that was aimed at exploring Malaysian primary school boys' and girls' literacy achievement. In this part of the study, the perceptions of the Bahasa Malaysia teachers were sought as to whether the boys and girls had different attitudes toward reading. Data in this qualitative study were gathered from focus group interviews with Malaysia teachers, as well as from the teachers' reflections or journal entries that documented their personal perceptions, ways of dealing with students, and their suggestions on teaching boys and girls. The findings suggest that the teachers were generally aware of the difference in the attitudes of boys and girls toward reading, but do not employ specific teaching strategies to address the issue.